The significance of the amorphous potential energy landscape for dictating glassy dynamics and driving solid-state crystallisation. Issue 44 (2nd November 2017) - Ruggiero, Michael T.; Krynski, Marcin; Kissi, Eric Ofosu; Sibik, Juraj; Markl, Daniel; Tan, Nicholas Y.; Arslanov, Denis; van der Zande, Wim; Redlich, Britta; Korter, Timothy M.; Grohganz, Holger; Löbmann, Korbinian; et al.
Abstract : We show clear evidence for a theory proposing that the shape and structure of the PES is the fundamental factor underlying the dynamics at temperatures below the glass transition. Abstract : The fundamental origins surrounding the dynamics of disordered solids near their characteristic glass transitions continue to be fiercely debated, even though a vast number of materials can form amorphous solids, including small-molecule organic, inorganic, covalent, metallic, and even large biological systems. The glass-transition temperature, T g, can be readily detected by a diverse set of techniques, but given that these measurement modalities probe vastly different processes, there has been significant debate regarding the question of why T g can be detected across all of them. Here we show clear experimental and computational evidence in support of a theory that proposes that the shape and structure of the potential-energy surface (PES) is the fundamental factor underlying the glass-transition processes, regardless of the frequency that experimental methods probe. Whilst this has been proposed previously, we demonstrate, using ab initio molecular-dynamics (AIMD) simulations, that it is of critical importance to carefully consider the complete PES – both the intra-molecular and inter-molecular features – in order to fully understand the entire range of atomic-dynamical processes in disordered solids. Finally, we show that it is possible to utilise this dependence to directly manipulate and harness amorphous dynamics in order to control the behaviour of such solids by using high-powered terahertz pulses to induce crystallisation and preferential crystal-polymorph growth in glasses. Combined, these findings provide compelling evidence that the PES landscape, and the corresponding energy barriers, are the ultimate controlling feature behind the atomic and molecular dynamics of disordered solids, regardless of the frequency at which they occur.